Simulation analysis for maximizing renewable solar energy to improve the power generation capacity in the state of Kuwait - Muhaisen, Naser; Khan, Sheroz; Ismail, Zeyad M. A.; Habaebi, Mohamed Hadi; Ahmed, Nabil A.; Ahmed, Musse Mohamud (IEEE, 2018)
This paper aims to present how to improve power generation capacity in the State of Kuwait through simulation analysis for maximizing the usage of renewable energy applications. Power demand in Kuwait increases every year by 6% that causes load-shedding problems in the national utility grid system. An effective solution is proposed in this paper to enhance the power demand shortage which leads to reduce the effects of load demands excesses, by employing some solutions in the field of solar energy system. The on-grid solar energy system to be spread on roof of buildings connected to utility grid in Kuwait is a fantastic solution for backing up the increasing power demand. In this paper, the research work is directed towards the study of new approach by adopting power generation system based on PV on-grid systems installed on rooftops of commercial and residential buildings. The system performance analysis is carried out by choosing Mono crystalline PV modules using PSIM software simulation. This simulation covers the analysis of power generated by the PV system as an input passing through a selected maximum power point tracker (MPPT) to achieve the maximum energy output. A control algorithm for power regulation has been developed with maximum power generation of enhanced AC power grid with power factor close to unity. A reliable tracker for the power output was shown by the simulation results generated by the model.